A utilização de jogos no ensino da hidrostática - Oliveira, Rerison de Sousa (2023)
This dissertation seeks to contribute to the teaching process, working in a playful way through online games within specific sites of competition and, mainly, for teaching. Wordwall and Kahoot were the sites used in this work for teaching physics with distributed concepts in some topics of hydrostatics. We follow some steps within a didactic sequence that basically consists of collecting information based on the students' experiences and their previous knowledge, based on the significant learning of Ausubel. A next step was to develop a game based on this information and then apply this activity, with the collected data the teacher performs a didactic intervention to work on the points that still showed deficiency, and this process can be repeated as many times as necessary. The methodology applied in collecting information about the learned concepts is based on familiarizing the games of today's young generation, as this is constant in the students' lives. To test the didactic sequences with the two sites, we worked with up to 173 students from four different classes. The analysis of the correct answers to the questions with hydrostatic concepts explored in the didactic sequences were obtained from tools on the websites themselves, which facilitated the analysis of the results. The didactic sequences are easy to apply and the idea can be extended to other physics topics.